Implementing The Values Of Raḥmatan Li Al-‘Ālamīn Through Maqāṣid-Based Exegesis To Achieve Social Justice - Bustamam, Risman; Hardivizon, Hardivizon (Jurnal Ushuluddin, 2025)
This article aims to examine the implementation of raḥmatan li al-‘ālamīn values through Maqāṣid-Based Interpretation (Tafsīr maqāṣidī) in the context of social justice, based on QS. Al-Anbiyā’ verse 107. The study employs a qualitative method with a literature review approach and textual analysis of classical and contemporary exegesis literature. The findings reveal that the value of raḥmatan li al-‘ālamīn is not only theological but also serves as a practical guide for fostering a just, harmonious, and prosperous society. Tafsīr maqāṣidī, which emphasizes the objectives of Islamic law (maqāṣid al-sharī‘ah) such as the protection of religion, life, intellect, lineage, and wealth, provides a comprehensive framework for translating Islamic values into social policies relevant to modern challenges. The study also identifies key challenges in implementing these values, including social, economic, political, and cultural barriers, while offering practical opportunities and strategies to overcome them. In conclusion, raḥmatan li al-‘ālamīn values, through Tafsīr maqāṣidī, can be effectively integrated into social policies to address various global challenges, offering inclusive and equitable solutions. This study is expected to serve as a reference for academics, policymakers, and practitioners in promoting Islamic values as a mercy for all creation